La gestión del cliente del Servicio Técnico el Compin en la Parroquia Febres Cordero, cantón Babahoyo, Provincia de Los Ríos - Castro Vargas, Clarisa de Jesús (2021)
This case study consists of analyzing the management of the client applied by the technical service “Compin” of the Febres Cordero parish, Babahoyo canton, Los Ríos province in order to determine the shortcomings that exist during the process of attention to the users due to the lack of satisfaction strategies that influence the profitability of the company. For the development of this research, the use of a descriptive-bibliographic methodology is implemented and with the help of techniques and instruments such as interviews and surveys to be used for data collection. Each of the particularities found will be analyzed based on previously made theoretical supports, in order to correctly conclude the objective of the work presented and validate the data provided in the current document.